A practical three-dimensional wheel-rail interaction element for dynamic response analysis of vehicle-track systems. (1st October 2021) - Liu, Yongdou; Montenegro, Pedro A.; Gu, Quan; Guo, Wei; Calçada, Rui; Pombo, João
Highlights: A practical 3D wheel-rail (WR) interaction element with nodes of WR is developed. FE model of vehicle-track system keeps unchanged without iterative subsystems. Piecewise linear representation of WR profiles allows efficient WR contact search. Robust curvature fitting technique avoids discontinuities of the WR contact force. Multiple contact points and flange-contact scenarios can be considered. Abstract: A novel practical three-dimensional (3D) wheel-rail interaction (WRI) element is developed to simulate the interaction between a fast-moving wheel node and nodes of the rail. Different from most previous methods of wheel-rail contact in multibody dynamics, the wheel-rail relationship in this paper is simulated by the WRI element. The WRI element is implemented into a general finite element software framework (i.e., OpenSees), which allows us study not only the vehicle behavior as the multibody models allow, but also the structure behavior with any degree of complexity. Implemented in a FEM framework with strong nonlinear capabilities, it also allows us to study scenarios with important nonlinearities. Compared to most existing models, the WRI element has a better compatible property and can be easily added to the vast majority of finite element platforms. The wheel-rail contact geometry is calculated efficiently with wheel/rail profiles fitted through linear curves and contact locations solved through algorithms with a higher efficiency. Local curvatures around contact points are calculated differently to avoid discontinuities of the contact force. Movements of a wheelset and of a train are studied to verify the accuracy and capability of the WRI element in the dynamic simulation of vehicle-track systems.